PPU-friendly Biomechanical Models for Virtual Medicine - Qin, Jing; Chui, Yim-Pan; Ho, Simon Sze-Ming; Poon, Wai-Sang; Heng, Pheng Ann (International Journal of Virtual Reality, 2009)
The main focus of virtual medicine is to develop and deliver virtual reality based training and computer enhanced learning in medicine. Traditionally, medical students learn diagnostic, therapeutic and surgical skills through difficult clinical training on live patients. With the change in the health economics, the advances of minimal invasive surgery (MIS) and shortening of hospitalization time, source and availability of patient for teaching become a major problem. Advanced technologies such as virtual reality, visualization and dedicated hardware accelerator for graphics or physics processing can help making the learning process more efficient, engaging and flexible. It is possible to construct immersive environments to provide realistic visualization and haptics feedbacks for anatomy education and surgical training. In this paper, we would like to share our experiences of using a newly released physics processing unit (PPU) in developing various virtual medicine applications in virtual orthopedic trauma surgery, ultrasound guide biopsy training, virtual neuro-endoscopy and telemedicine